The Effect of Product Innovation on Purchasing Decisions for Custom T-shirts with Quality as a Moderating Variable (Study on Sarkastem Lampung Tengah) - Ardiyana Pertiwi; Johannes P. Kumagaya; Irene Brainnita Oktarin (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
This study aims to prove whether product innovation affects purchasing decisions for custom t-shirts with quality as a moderating variable in Sarkastem Lampung Tengah. This study uses quantitative research methods. The sampling method used was purposive sampling with a sample size of 95 respondents. This study uses SEM-PLS (Structural Equation Modeling - Partial Least Squares) data analysis measurement tools with the SmartPLS program. The results of this study indicate that product innovation has a positive and significant effect on purchasing decisions and product quality can affect the relationship between product innovation and purchasing decisions, but in a negative direction, namely weakening the relationship between the two.